Financial Volatility Paradox in Philanthropic Organizations: Evidence from Indonesian Religious and Secular Nonprofits - Hermawan, Dedy; Fikri, Mohammad Ali; Pituringsih, Endar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the relationship between revenue concentration and financial volatility in philanthropic organizations, challenging the conventional assumption that diversification leads to greater stability. Using longitudinal data from 10 Indonesian philanthropic organizations registered with Perhimpunan Filantropi Indonesia over a 10-year period (2015-2024), this research compares income volatility patterns between religious-based and secular nonprofits. The findings reveal a counterintuitive paradox: religious organizations with concentrated revenue sources (zakat, infaq, and sadaqah) demonstrate significantly lower volatility (16.4%) compared to secular organizations with more diversified funding (53.4%). Mann-Whitney U test confirms this difference is statistically significant (U = 2.000, Z = -2.193, p = 0.028). This study introduces the concept of 'normative income stability' where religious obligations create a baseline donation pattern that is more stable than voluntary giving, thereby extending Financial Vulnerability Theory by proposing that the nature of income source moderates the diversification-stability relationship. The implications suggest that nonprofit financial management strategies should consider institutional characteristics rather than pursuing universal diversification.